2003
DOI: 10.1108/02683940310484035
|View full text |Cite
|
Sign up to set email alerts
|

Brainsex and occupation: the role of serendipity in the genesis of an idea

Abstract: This paper sets out the events that led to the development of the hypothesis that brains are sexed and that this, at least in part, underlies the sex differentiation that is observed across the range of occupations. It is also suggested that an individual's brainsex is a powerful organising influence on his or her pattern of abilities, emotional life, motives, and interests. It therefore follows that choice of occupation is an indicator of an individual's essential psychological character. The roll played by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The study suggested that women exposed to high PT, represented by a relatively low 2D:4D, were more likely to be found working in such occupations, and vice versa. For some gender-dependent traits such as dichotic listening tasks, synonym generation and spatial tests, male-typical scores have been reported among women engaged in male-typical occupations and female-typical scores among women in femaletypical occupations (Govier, 2003). This also suggests that male-typical qualities are likely to be related to occupational choice among females.…”
Section: Discussionmentioning
confidence: 98%
“…The study suggested that women exposed to high PT, represented by a relatively low 2D:4D, were more likely to be found working in such occupations, and vice versa. For some gender-dependent traits such as dichotic listening tasks, synonym generation and spatial tests, male-typical scores have been reported among women engaged in male-typical occupations and female-typical scores among women in femaletypical occupations (Govier, 2003). This also suggests that male-typical qualities are likely to be related to occupational choice among females.…”
Section: Discussionmentioning
confidence: 98%
“…The Jungian concept of "synchronicity", i.e. the occurrence of meaningful coincidences in time, may be relevant in the discovery of a career path (Guindon & Hanna, 2002), the genesis of an idea (Govier, 2003) or an opportunity for a new venture creation (Baker, Miner & Eesley, 2003).…”
Section: The Process Of Serendipitymentioning
confidence: 99%
“…A lower 2D:4D was found to be associated with more enterprising careers among women (Weiss et al 2007). Low 2D:4D was found in individuals engaged in male-dominated occupations and this phenomenon was particularly prominent among females, indicating that PT might have a stronger relationship with occupational choice in women (Govier 2003;Manning et al 2010). In another study, financial risk-taking preferences were positively correlated with testosterone levels among female students, but not among males (Sapienza et al 2009).…”
Section: Discussionmentioning
confidence: 91%